2012
DOI: 10.1016/j.virol.2011.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsins B and L activate Ebola but not Marburg virus glycoproteins for efficient entry into cell lines and macrophages independent of TMPRSS2 expression

Abstract: Ebola (EBOV) and Marburg virus (MARV) cause severe hemorrhagic fever. The host cell proteases cathepsin B and L activate the Zaire ebolavirus glycoprotein (GP) for cellular entry and constitute potential targets for antiviral intervention. However, it is unclear if different EBOV species and MARV equally depend on cathepsin B/L activity for infection of cell lines and macrophages, important viral target cells. Here, we show that cathepsin B/L inhibitors markedly reduce 293T cell infection driven by the GPs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(105 citation statements)
references
References 50 publications
6
94
1
1
Order By: Relevance
“…Of note, α5β1 integrin is required for cathepsins B and L to be catalytically active for GP priming [49], supporting an earlier study showing the importance of integrins for filovirus entry [50]. However, since each filovirus species has a different dependency on cathepsin-processing [51,52] and mouseadapted ebolavirus retains full pathogenicity in mice deficient in either cathepsin B or L [53], other important host proteases are likely involved in proteolytic processing of GPs.…”
Section: Entrysupporting
confidence: 62%
“…Of note, α5β1 integrin is required for cathepsins B and L to be catalytically active for GP priming [49], supporting an earlier study showing the importance of integrins for filovirus entry [50]. However, since each filovirus species has a different dependency on cathepsin-processing [51,52] and mouseadapted ebolavirus retains full pathogenicity in mice deficient in either cathepsin B or L [53], other important host proteases are likely involved in proteolytic processing of GPs.…”
Section: Entrysupporting
confidence: 62%
“…Conversely, the fact that the other 19 compounds affected only MARV indicates that specific differences in cell entry may be exploited in studying infection mechanisms unique for each virus. Indeed, this is supported by work showing that each virus has different dependencies on cellular proteases for activation of the GP for membrane fusion (22,23) and is potentially the reason that none of the broadly active compounds were found to be cathepsin protease inhibitors.…”
Section: Discussionmentioning
confidence: 94%
“…Filoviral GP binds receptors, and the virus is internalized through macropinocytosis (18,19) and trafficked through endosomes, which is dependent on the calcium channel TPC2 (14,20). During trafficking the virus is exposed to an increasingly acidic environment, in which proteases are activated and cleave the GP (21)(22)(23)(24), allowing interaction with NPC1, a key protein found in endosomes (25,26).…”
mentioning
confidence: 99%
“…Selective inhibitors of cathepsin B (e.g., CA-030, CA-074, CA-074Me) and cathepsin L (e.g., E-64c) could serve as potential candidates in the therapy of EVD [37,38]. However, Marzi et al [39] demonstrated that these two enzymes weren't necessary for virus entry and replication.…”
Section: Inhibitors Of Virus Entry and Fusionmentioning
confidence: 99%